Pengaruh Promosi Kesehatan Dengan Media Video Terhadap Pengetahuan Hipertensi Pada Masyarakat Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu: Promosi Kesehatan - Gunawan, Deni (Poltekkes Kemenkes Bengkulu, 2023)
Hypertension is defined as systolic blood pressure equal to or above 140 mmHg and or diastolic blood pressure equal to or above 90 mmHg. Some of the factors that cause hypertension are caused by unhealthy lifestyles such as smoking, obesity, consuming alcohol, physical activity and psychosocial stress. The purpose of this study was to determine the effect of the effect of health promotion by video media on knowledge of community hypertension in the working area of Telaga Dewa Health Center in 2020. The type of research used was a pre experiment with one group pre-test-post-test design. The sample in this study was 41 people in the working area of the Telaga Dewa Health Center in Bengkulu City. Analyzed usingtest Wilcoxon.test results Wilcoxon obtained p value = 0.000 ≤ 0.05 means significant, which means there is an effect of health promotion by video media on the knowledge of hypertension in the community in the Telaga Dewa Health Center in Bengkulu City. It is recommended for health centers where research can provide hypertension health promotion using video media to the community so that public knowledge.